FUNDAMENTAL RIGHTS OF PERIPHERAL CONSTITUTIONS: A NEW THEORETICAL APPROACH AND THE ZIKA VIRUS IN BRAZIL - Wálber Araujo Carneiro (BRICS Law Journal)
This essay proposes a new theoretical model directed towards the observation of fundamental rights present in the Constitutions of peripheral States. Parting from a critical revision of classic perspectives oriented by the dogmatic affirmation of fundamental rights and the institutional tradition derived from sociological observation, these rights perform a dual function. They are responsible for the structuring of normative expectations and, at the same time, they construct internal dogmatic limits within the system. Through the contributions of phenomenology and social systems theory, this model suggests autonomous spheres of fundamentality in contrast to the classical unity of fundamental rights. Furthermore, the balancing schemes are substituted for an internal “law of collision.” Conflict resolution undergoes a shift from the traditional method to the system’s reflexive pragmatics, contributing to the legal security and the democratic legitimacy of judicial review. Finally, it verifies how this theory could be applied to the advent of the Zika virus which affected Brazil from 2015 to 2017. As the Zika virus crisis involves different spheres of fundamentality, entailing a range of systems of law and therefore revealing different collision patterns, this essay demonstrates how this new approach could contribute to the control of solutions.